Formulasi Dewan Tripartit Industri Maritim dan Ratifikasi Konvensi International Labour Organization Nomor 188 Tahun 2007 Tentang Pekerjaan Dalam Penangkapan Ikan - Nadiya Nurmaya; Bima Prakoso (Universitas Airlangga, 2022)
AbstractProtecting the Indonesian Fisheries Crews (ABK) is an urgent matter considering that the government has not been optimal in providing protection so far. This situation can be momentum to clarify the rights of the Indonesian Fisheries Crews (ABK). This study aimed to determine the extent of the government’s efforts in protecting Indonesian Fisheries Crews (ABK). The research method used in this study was normative juridical with the types of statutory, conceptual, and comparative approaches. The results of the study indicated that the Law on Protection and Placement of Indonesian Workers, the Law on the Protection of Indonesian Migrant Workers, and Regulation of the Minister of Marine Affairs and Fisheries Number 35/PERMEN-KP/2015 have not explicitly regulated the special protection for Indonesian Fisheries Crews. On the other hand, the weak supervision of the manning agency as a recruitment agency that initiated the occurrence of human rights violations in Indonesian Fisheries Crews has made Indonesian Fisheries Crews feel that their rights have not been optimally protected. Thus, the phenomenon of the high number of cases of modern slavery practices has become the task of the government to repair several existing mechanisms and instruments of legislation. AbstrakPemberian perlindungan terhadap para ABK Perikanan Indonesia merupakan hal yang mendesak mengingat sejauh ini pemerintah masih belum optimal dalam memberikan perlindungan. Keadaan ini dapat menjadi momentum untuk memperjelas hak para ABK Perikanan Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif dengan jenis pendekatan peraturan perundang-undangan, konseptual, dan perbandingan. Hasil penelitian menunjukkan bahwa Undang-Undang Perlindungan dan Penempatan Tenaga Kerja Indonesai, Undang-Undang Perlindungan Pekerja Migran Indonesia, dan PERMEN Nomor 35/PERMEN-KP/2015 belum mengatur secara eksplisit mengenai perlindungan khusus bagi ABK Perikanan Indonesia. Disisi lain, lemahnya pengawasan terhadap manning agency sebagai biro agen perekrutan yang mengawali terjadinya pelanggaran Hak Asasi Manusia pada ABK Perikanan Indonesia membuat para ABK Perikanan Indonesia merasa hak-haknya belum secara optimal dilindungi. Dengan demikian, fenomena tingginya jumlah kasus praktik modern slavery sampai saat ini menjadi tugas bagi pemerintah untuk melakukan reparasi beberapa mekanisme dan instrument peraturan perundang-undangan yang ada.